The effect of Commissioner Board's Characteristics on the Firm Value - Dr. Edy Supriyono, M.Si (International Conference on Industrial Revolution for Polytechnic Education, 2019)
This study aims to determine the relevance of the Characteristics of the Board ofCommissioners and the value of non-financial public corporations in the Indonesia StockExchange. This research is driven by the importance of corporate value and the Characteristicsof the Board of Commissioners in Indonesia. The Company's Value and Characteristics of theBoard of Commissioners in Indonesia are increasingly important as many companies are notable to maintain the value of the company despite having a qualified Board of Commissioners.This research is original because this research hypothesis is different from previous researchhypothesis. The hypothesis of this study assumes no influence of the board of commissioners onthe value of the company.Using secondary data from annual reports published on the Indonesia Stock Exchange in2009 to 2013. With the population of 1280 observations, this study collects the sample of 525observations. Processing data of this study uses the regression method by IBM SPSS 20thversion.The study found that the size of the Board of Commissioners, the educationalbackground of members of the board of commissioners, the international experience of membersof the board of commissioners, and the industry knowledge of the members of the board ofcommissioners have no effect on the value of the company. The proportion of independent boardof commissioners influences the value of the company. The number of board meetings and theexperience of members of the Board of Commissioners negatively affect the value of the company.